Simulation of one dimension shock initiation of condensed explosive by SPH method. Issue 2 (18th April 2016) - Yang, Gang; Liu, Rangqi; Hu, De'an; Han, Xu
Abstract : Purpose: – The purpose of this paper is to study the ability of SPH method in simulating shock initiation process. The initiation and subsequent explosion processes of condensed explosive involve high-pressure propagation and material large deformation, which increase the simulation difficulty in using traditional mesh-based method. The study aims to take the SPH method as an alternative method to shock initiation simulation. Design/methodology/approach: – The SPH method combined with some correct aspects is applied to simulate the shock initiation process. The condensed explosive is ignited by the impact of high-speed flyer. In order to avoid the non-physical penetration between particles of high-velocity flyer and condensed explosive, a particle to particle contact algorithm is employed. After the ignition, the detonation process of condensed explosive is represented by the ignition and growth model. A modified SPH method based on Riemann-solver is applied to smooth the numerical oscillation at shock front. Two numerical examples are implemented to illustrate the capability of SPH method in shock initiation simulation. One is the interface velocity experiment of PBX-9501. Another is the plate push experiment of PBX-9502. Both of the examples include the shock initiation process of condensed explosive. Findings: – Numerical results show that the shock initiation process of condensed explosive can be well predicted by SPH method. The characteristics of detonation are captured in the simulation. The measured data in numerical examples are also in good agreement with the experimental data. Research limitations/implications: – Because of the research purpose is to study the ability of SPH for shock initiation simulation, only one dimension numerical examples are discussed in the paper. Therefore, researchers are encouraged to extend and test the proposed method to two or three dimension shock initiation problems simulation. Originality/value: – This paper provides an alternative method for shock initiation simulation. The implemented method can overcome the weaknesses of traditional mesh-based method in simulation of shock initiation problems.